Pemberdayaan Perempuan Melalui Pelatihan Salon di UPT Pelayanan Sosial Tuna Rungu Wicara dan Lanjut Usia Pematang Siantar Dinas Sosial Provinsi Sumatera Utara - Ade Indah Hutasoit; Maria Luciana Sinuhaji; Arya Pranata Sidabutar; Hairani Siregar (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Empowerment has a very important role in improving the quality of life and social welfare, especially for marginalized groups such as deaf and speech-impaired women and the elderly. This research aims to explore women's empowerment through salon training carried out at the UPT Social Services for the Deaf, Speech and Elderly Pematang Siantar, North Sumatra Province Social Service. This salon training is designed to provide practical skills that can help deaf-mute and elderly women increase their economic independence and improve their standard of living. The method used is a qualitative approach with observation and interviews as data collection techniques. The research results show that salon training not only provides technical skills but also increases participants' self-confidence, expands their social networks, and opens up job opportunities. Overall, this program contributes to women's empowerment by creating opportunities for them to become economically and socially independent. This research provides recommendations for the development of similar training programs in the future to expand the positive impact on communities of women in need.